Computer simulation of the mechanism for the synthesis of carbonado diamond - João José de Assis Rangel; Ruben Rosenthal; Guerold Sergueevitch Bobrovnitchii; Sergio Neves Monteiro (Materials Research, 2006)
The synthesis mechanism associated with the formation of carbonado type polycrystalline diamond has been analyzed. This analysis was performed by computer simulation of the field of temperature developed at the moment of graphite transformation into polycrystalline diamond. It was found that during the synthesis of this carbonado diamond, a strong non-steady thermal condition occurs, leading to changes in the thermodynamic equilibrium. As a consequence, a region comprising non-transformed graphite and carbonado with different characteristics is established. An experimental comparison was carried out between the carbonado hardness profile and the field of temperatures. The results show that the higher the temperature attained at local points inside the high-pressure chamber, the higher the hardness of the diamond. The simulation and experimental results indicated that concurrent mechanisms are acting during the carbonado synthesis.